The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cpe.7183
|View full text |Cite
|
Sign up to set email alerts
|

Load balancing techniques for fog computing environment: Comparison, taxonomy, open issues, and challenges

Abstract: SUMMARY Load balancing (LB) is nothing but the systematic distribution of load over different servers. The fog server is handling the maximum data of the cloud server to enhance the advancement of users' requests. The growth in data requests is escalating, and fog computing has intensified the accessibility of the data. Fog computing achieves many challenges according to the demands of the users, but even so, some challenges require more progress. The problem faced by fog computing is LB due to an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Furthermore, the FC network might address the distance between edge devices and the cloud by placing servers near the edge to significantly decrease energy consumption and latency. In this situation, task offloading decisions between the machines at the border and FNs are influenced by the available resources, energy usage on offloading, and network load balancing 10 . Fog computing encounters several difficulties with increased IoT devices and service requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the FC network might address the distance between edge devices and the cloud by placing servers near the edge to significantly decrease energy consumption and latency. In this situation, task offloading decisions between the machines at the border and FNs are influenced by the available resources, energy usage on offloading, and network load balancing 10 . Fog computing encounters several difficulties with increased IoT devices and service requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, task offloading decisions between the machines at the border and FNs are influenced by the available resources, energy usage on offloading, and network load balancing. 10 Fog computing encounters several difficulties with increased IoT devices and service requirements. The other issues arise when several IoT devices request a service, which poses numerous challenges, such as increased latency, energy usage, and so forth.…”
mentioning
confidence: 99%
“…Several methods based on LB are discussed in this survey [20], which overcomes the problem of overloaded data on the network. Latency, bandwidth, deadlines, cost, security, execution time, and execution time are some of the aspects that authors have focused on in LB.…”
Section: Related Workmentioning
confidence: 99%
“…𝑓𝑑 𝑗 𝑤 = 𝑓𝑑 𝑗 𝑟 * 𝑤 𝑞 + 1 𝑃𝑇 𝑖𝑗 𝑡 * 𝑤 𝑒 (20) where𝑓𝑑 𝑗 𝑟 is the rank of fdj, wqand we are the weight of fog device rank and the weight of task processing time respectively, such that wq+ we = 1.…”
Section: Phase 3: Determining Fog Device Weightmentioning
confidence: 99%
“…Liu et al [12] demonstrated a fog-based privacy-preservation scheme for SG data aggregation that enables the service provider for multiple function queries on encryption of meter data. The authors of [20][21][22][23][24] have worked on IoT applications and events where Markov model has been used. However, none of them is suitable for a smart grid environment.…”
Section: Related Workmentioning
confidence: 99%